TRANSFORMASI PERAN PENGAWAS SEKOLAH DI KECAMATAN CILEDUG KABUPATEN CIREBON - Abdurakhman, Abdurakhman; Patimah, Siti; Warisno, A; Hidayah, Nur; Arafah, A Latif Arung (Ibn Khaldun University, Bogor, 2025)
The transformation of the role of school supervisors into one of the change agendas is very necessary to support the realization of student-centered learning through the mentoring cycle. The mentoring referred to is the activity of school supervisors working with school principals in increasing the capacity and quality of education unit services to carry out student-centred learning using relevant strategies and methods. Assistance of school supervisors in implementing the school principal's progress achievements as an implementation of the commitment of the head of the educational unit of each assisted school in realizing their school's work program. This activity is carried out through discussions, interviews and recorded results are expressed in the form of data processing instruments according to the results obtained by each -each head of educational unit. The aim of this writing is to provide a comprehensive overview of the implementation of supervisory duties in supporting the development and improvement of the quality of education in educational units. This study is divided into seven parts, namely: 1) Progress of Educational Report Card achievements, 2) Progress of development of infrastructure, 3) Progress of PTK competency development, 4)Progress of Student Competency Development, 5) Academic/non-academic achievement of Persetadik and PTK, 6) Data-Based Planning, Preparation of RKT/RKAS documents, and 7)Preparation of Education Unit Curriculum Documents. Conclusion: The mentoring that has been implemented in 18 educational units/facilitated schools has succeeded in making a positive contribution to improving the quality of learning, both in terms of curriculum, teacher competency, school management and infrastructure development.